Dropped Head Syndrome Treated with Physical Therapy Based on the Concept of Athletic Rehabilitation - Toshio Mori; Kentaro Mataki; Yukiyo Shimizu; Kai Matsuba; Kosei Miura; Hiroshi Takahashi; Masao Koda; Hiroshi Kamada; Masashi Yamazaki (Case Reports in Orthopedics)
Patients with dropped head syndrome (DHS) show severe cervical kyphosis, i.e., chin-on-chest deformity, and their activities of daily living are impaired considerably. However, the therapeutics for DHS, especially conservative treatment, have not been fully established. A 75-year-old woman suffered from DHS, which she developed from neck pain due to cervical spondylosis. Examinations showed atrophy and dysfunction of her cervical extensor muscles. For this patient, we created a special program of physical therapy based on the concept of athletic rehabilitation and provided her the athletic rehabilitation-based physical therapy (AR-PT). After starting AR-PT, the patient’s neck pain was relieved. She recovered from DHS, and the atrophy of her cervical extensor muscles improved. This study suggests that our program of AR-PT improves cervical extensor muscle insufficiency in patients with DHS and corrects their cervical kyphosis.